2017
DOI: 10.1007/s11606-017-4193-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Hospital Performance on the Hospital-Wide 30-Day Readmission Metric: Is the Playing Field Level?

Abstract: A number of hospital-level characteristics (such as academic tertiary care center status) were significantly associated with worse performance on the CMS-calculated HWR metric, which may have important health policy implications. Until the reasons for readmission variability can be addressed, reporting the current HWR metric as an indicator of hospital quality should be reevaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Listing assessments (Hospital Compare, IBM, Joint Commission) indicated hospital quality without comparison to other hospitals. Lastly, evaluation-based studies [ 20 – 25 ] provided critical examinations of hospital performance assessment methodologies from Hospital Compare [ 21 , 23 , 24 , 35 ] and US News [ 21 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Listing assessments (Hospital Compare, IBM, Joint Commission) indicated hospital quality without comparison to other hospitals. Lastly, evaluation-based studies [ 20 – 25 ] provided critical examinations of hospital performance assessment methodologies from Hospital Compare [ 21 , 23 , 24 , 35 ] and US News [ 21 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A suggested reason for this difference is that performance may be skewed by factors not directly related to quality such as patient volume, where high-volume facilities had better ratings [ 23 ]. Moreover, a number of other hospital-level characteristics, such as academic tertiary care center status [ 35 ], have been associated with poor performance on CMS-calculated metrics [ 17 , 35 ]. These examples demonstrate that no assessment methodology is perfect, but each has its own set of strengths to inform their intended audience for the improvement of care and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resident physicians at academic centers may be more inclined to readmit patients rather than send them to the emergency department when a postdischarge complication occurs. 17 Teaching hospitals may also perform more complex operations owing to the availability of specialists and patient resources, a factor not addressed in our analysis. 18 The literature on nurse staffing ratios is inconsistent with respect to readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is linked to financial penalties. 15,16 Decreasing readmission provides an exclusive opportunity for improving quality and for reducing costs, and it is considered a priority in quality improvement. 17 Some studies have shown that most readmissions are preventable; reducing readmission rates is considered a factor for improving quality in the future.…”
mentioning
confidence: 99%